Deadly persuasion the advertising of alcohol and tobacco - Kilbourne, Jean; Jhally, Sut; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2003)
Jean Kilbourne exposes the manipulative marketing strategies and tactics used by the alcohol and tobacco industries to keep Americans hooked on their dangerous products
Title from title screen
A lecture by Jean Kilbourne
Camera, Kelly Garner, Teri Morris, Jeremy Smith ; editors, Sut Jhally, Kenyon King, Jeremy Smith ; original music, Thom Monahan ; graphics, shannon McKenna
Presenter: Jean Kilbourne
Keywords: Advertising -- methods; Tobacco Industry; Alcohol-Related Disorders; Alcoholic beverages